Recent results in accelerator mass-spectrometer construction at BINP - Rastigeev, S.A.; Alinovsky, N.I.; Goncharov, A.D.; Klyuev, V.F.; Konstantinov, S.G.; Kryuchkov, A.M.; Parkhomchuk, V.V.; Petrichenkov, M.V.; Reva, V.B. (Вопросы атомной науки и техники, 2008)
Present status of the accelerator mass spectrometry facility at BINP is described. The results of first experiments for ¹⁴C selection and background measurements are presented.